A ball milling method for improving volume stability and firmness of steel slag aggregate
Patent Information
- Application Number
- CN202611399899.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-13
AI Technical Summary
[0006]因此,游离氧化钙易与水汽和二氧化碳发生化合反应,并生成Ca(OH)2和CaCO3等化合物,由于钢渣上存在较多的游离氧化钙,造成钢渣集料的体积安定性不良,阻碍了钢渣集料在道路建设工程中的大规模推广与应用
1、本发明利用钢渣内部矿物硬度差异,实现游离氧化钙的物理脱除:
Smart Images

Figure CN122895073A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of road engineering materials technology, and in particular to a ball milling method for improving the volume stability and robustness of steel slag aggregate. Background Technology
[0002] Steel slag originates from waste generated in the iron and steel smelting industry, accounting for approximately 12% of steel production. With the rapid development of the steel industry, the amount of steel slag produced has also increased significantly. The large-scale stockpiling of steel slag not only wastes land resources but also causes irreversible pollution to the ecological environment. Therefore, the treatment and resource utilization of steel slag has gradually become a research hotspot. Currently, due to its abundant angularity and low crushing value, steel slag is mainly recycled as road aggregate.
[0003] Steel slag aggregate is formed by the condensation of steel slag waste liquid and contains various compounds such as dicalcium silicate (C2S), tricalcium silicate (C3S), magnesium oxides, iron oxides, and calcium oxides (CaO). The temperature at which the steel slag waste liquid forms is approximately 1600℃~1700℃. At this temperature, some of the lime particles involved in steelmaking are still unmelted, and the calcium oxide crystals contained within these lime particles float or are submerged in the waste liquid. Some of the calcium oxide crystals in the lime particles react with SiO2 in the waste liquid to form C3S; others remain in a free state, forming free calcium oxide (f-CaO). When the temperature of the waste liquid decreases to 1500℃~1600℃, some magnesium oxide crystals preferentially precipitate. When the temperature drops to 1300℃~1500℃, C2S and C3S crystals begin to precipitate. As the temperature of the waste liquid decreases to around 500℃, the RO phase (FeO, MgO) composed of divalent metal oxides begins to form, and some C3S decomposes into free calcium oxide and C2S. The precipitation behavior of free calcium oxide crystals and the formation process of the aforementioned compound crystals in steel slag indicate that the distribution of compound components inside the steel slag aggregate is extremely uneven. This means that some parts of the steel slag aggregate may be rich in C2S, C3S, and free calcium oxide, while the rest is rich in the RO phase.
[0004] Traditional methods for reducing the free calcium oxide content in steel slag mainly involve aging and acidification. Aging utilizes the hydration reaction of water vapor with calcium oxide in the natural environment. Although simple to operate, the treatment cycle is extremely long, typically requiring more than six months of stockpiling time, severely restricting the resource utilization efficiency of steel slag. Acidification removes free calcium oxide from steel slag through a rapid neutralization reaction between acid and calcium oxide. Despite its high processing rate, the high consumption of acid, the high corrosion resistance requirements of equipment, and subsequent wastewater treatment issues result in high overall treatment costs, making it difficult to promote on a large scale in industrial production.
[0005] It is worth noting that the Mohs hardness of C2S and C3S crystals is around 4.5, that of CaO crystals is 3-4, and that of iron oxides is 5.5-6.5. Therefore, steel slag contains both "easily grindable components" (C2S, C3S, and calcium oxide crystals) and "difficult-to-grind components" (iron oxides).
[0006] Therefore, free calcium oxide is prone to react with water vapor and carbon dioxide to form compounds such as Ca(OH)2 and CaCO3. Due to the presence of a large amount of free calcium oxide on steel slag, the volume stability of steel slag aggregate is poor, which hinders the large-scale promotion and application of steel slag aggregate in road construction projects. Summary of the Invention
[0007] This invention provides a ball milling method to improve the volume stability and robustness of steel slag aggregate, thereby overcoming the above-mentioned technical problems.
[0008] To achieve the above objectives, the technical solution of the present invention is as follows: A ball milling method for improving the volume stability and robustness of steel slag aggregate includes: S1: Steel slag aggregate with a particle size distribution range of the first particle size to the second particle size is placed into a planetary ball mill jar with a material-to-ball mass ratio of 0.1 to 1.3. The material is ball-milled at a revolution speed of 400 rpm to 600 rpm and a revolution-to-rotation speed ratio of 1:1 for 5 min to 15 min. S2: After ball milling, the steel slag aggregate is screened to separate the hard components whose particle size still falls within the original set gradation range, thus obtaining steel slag aggregate with improved volume stability and strength; wherein, any combination of the material-ball mass ratio, revolution speed and ball milling time satisfies the following conditions: the content of free calcium oxide in the hard components is not higher than 1.1% and the crushing value is not higher than 18%.
[0009] Furthermore, the ball milling time for each ball mass ratio and each revolution speed can be determined in the following ways: Select a combination of ball mass ratio and revolution speed within the range of ball mass ratio of 0.1 to 1.3 and revolution speed of 400 to 600 rpm; For the same selected combination of ball mass ratio and revolution speed, multiple ball millings were performed for different durations within 5 min to 15 min, and samples were taken to detect the free calcium oxide content, crushing value, roundness of the hard component, and the free calcium oxide content of the fine powder under sieve. Determine whether the lowest value of the free calcium oxide content of the hard component is not higher than 1.1%, whether the lowest value of the crushing value is not higher than 18%, and whether the values are within the preset range. If any value exceeds the set value, the combination of the material ball mass ratio and the revolution speed is marked as an invalid combination. For combinations that fall within the numerical range, with the ball milling duration as the independent variable, the evolution curves of the above four indicators as a function of ball milling time are fitted respectively. The ball milling times corresponding to the lowest point of free calcium oxide content in the hard component, the lowest point of crushing value, the lowest point of roundness, and the highest point of free calcium oxide content in the fine powder under the sieve are extracted, and the average value of the four is taken as the ball milling time of the combination.
[0010] Furthermore, the first particle size is 4.75 mm, and the second particle size is 16 mm.
[0011] Furthermore, the particle size of the fine powder is less than 4.75 mm.
[0012] Furthermore, the ball milling time for each combination of ball mass ratio and revolution speed was compared, and the combination of ball mass ratio and revolution speed corresponding to the minimum ball milling time was taken as the optimal process parameters for the ball milling treatment of steel slag aggregate.
[0013] Beneficial effects: This invention provides a ball milling method for improving the volume stability and robustness of steel slag aggregates, which has the following advantages: 1. This invention utilizes the difference in mineral hardness within steel slag to achieve the physical removal of free calcium oxide: Planetary ball mills crush materials through the mechanical collision and friction between grinding balls and the material. This invention is based on the significant hardness difference between the "easily grindable components" (C2S, C3S, and calcium oxide crystals, Mohs hardness 3-4.5) and the "difficult-to-grind components" (iron oxides, Mohs hardness 5.5-6.5) within steel slag. Through the combined revolution and rotation of the planetary ball mill jar, under conditions of a material-to-ball mass ratio of 0.1-1.3, a revolution speed of 400-600 rpm, and a milling time of 5-15 minutes, the easily grindable components rich in free calcium oxide are preferentially eroded and pulverized, while the harder iron oxide framework is retained. Subsequently, sieving separates the brittle fine powder enriched with free calcium oxide, reducing the free calcium oxide content in the hard components to below 1.1%. This method fully utilizes the inherent mineral composition characteristics of steel slag to achieve the physical removal of free calcium oxide without the need for chemical reagents, making it environmentally friendly.
[0014] 2. This invention achieves deep removal of free calcium oxide through a three-step mechanism of "stress concentration—crack propagation—stripping and screening": The ball milling process of this invention not only acts on the surface of steel slag aggregates but also separates most of the free calcium oxide crystals inside the aggregates through the following mechanisms: First, the continuous impact of the grinding balls on the steel slag aggregates generates stress and microcracks on the surface and near-surface region of the aggregates; second, as the ball milling continues, these microcracks gradually expand, exposing the free calcium oxide that was originally encapsulated by the calcium silicate phase; third, the tangential friction of the grinding balls peels the exposed free calcium oxide from the aggregate surface. For crushed aggregates with particle sizes smaller than a specified range (enriched with the peeled free calcium oxide), separation is achieved through manual sieving, ultimately reducing the free calcium oxide content of the steel slag aggregates within the original particle size range and improving their road performance. This three-step mechanism ensures that free calcium oxide is not only removed from the aggregate surface but also effectively separated from the aggregate interior, achieving deep removal.
[0015] 3. This invention significantly shortens the processing cycle and breaks through the efficiency bottleneck of aging treatment: Compared with traditional aging treatment (which requires more than six months of stockpiling time), this invention only requires 5 to 15 minutes of ball milling to reduce the free calcium oxide content of the hard component to below 1.1%, shortening the processing cycle from several months to tens of minutes, greatly improving the resource utilization efficiency of steel slag, and enabling steel slag aggregate to be quickly put into use in road construction projects.
[0016] 4. This invention avoids the costs and environmental burden of acidification treatment: This invention employs a purely physical method, requiring no acid solution, no corrosion-resistant equipment, and no acidic waste liquid. The overall treatment cost is far lower than that of acidification processes, making it suitable for large-scale industrial production and widespread application.
[0017] 5. This invention can simultaneously improve the mechanical properties of aggregates, ensuring road quality: This invention reduces the free calcium oxide content while selectively abrading easily grindable components and sieving out defective particles, ensuring that the crushing value of the hard components does not exceed 18%, thus significantly improving mechanical properties. The stripped steel slag aggregate possesses both low free calcium oxide content and high compressive strength, meeting the standard requirements for high-grade road aggregates. It fundamentally solves the problem of poor volume stability caused by the hydration expansion of free calcium oxide in steel slag aggregate, providing a reliable technical solution for the large-scale promotion and application of steel slag in road construction projects. Attached Figure Description
[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0019] Figure 1 A flowchart of a ball milling method for improving the volume stability and robustness of steel slag aggregate provided by the present invention; Figure 2 This is a schematic diagram of the motion stability state of the discrete element model of steel slag aggregate particles and grinding balls in this invention; Figure 3 A schematic diagram showing the correlation coefficients between the tangential collision energy loss of steel slag aggregate particles and the grinding ball model and the average roundness of the steel slag aggregate with the original gradation in the actual ball milling test. Figure 4 Schematic diagram of the normal and tangential collision energy loss of steel slag aggregate particles and grinding ball model under different working conditions; Figure 5 This is a schematic diagram of the surface morphology of untreated steel slag aggregate under a scanning electron microscope. Figure 6 This is a schematic diagram of the surface morphology of steel slag aggregate after ball milling, as seen under a scanning electron microscope. Figure 7 This is a schematic diagram of the average titration results of free calcium oxide content of two parallel samples of steel slag aggregate with a diameter of 13.2 mm to 16 mm at a revolution speed of 400 rpm, in an embodiment of the present invention. Figure 8 This is a schematic diagram of the average titration results of free calcium oxide content of two parallel samples of steel slag aggregate with a diameter of 9.5mm to 13.2mm, at a revolution speed of 400rpm, in an embodiment of the present invention. Figure 9 This is a schematic diagram of the average titration results of free calcium oxide content of two parallel samples of steel slag aggregate with a diameter of 4.75mm to 9.5mm, at a revolution speed of 400rpm, in an embodiment of the present invention. Figure 10 This is a schematic diagram of the XRD test results of crushed steel slag aggregate and fine steel slag powder in an embodiment of the present invention; Figure 11 This is a schematic diagram of the crushing value results of steel slag aggregate in an embodiment of the present invention. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] C2S, C3S, and f-CaO in steel slag are typically enriched on the surface of iron oxide particles. By utilizing the significant hardness differences between the different components, and effectively breaking down the weaker components while preserving the harder components relatively intact, and peeling them off from the surface of the steel slag aggregate, the shortcomings of traditional steel processing techniques can be overcome, promoting the large-scale and resource-based utilization of steel slag aggregate.
[0022] Mechanical grinding processes have great potential for controlling the properties of material surfaces. Ball milling, as an efficient and controllable physical surface treatment method, uses rotating grinding balls (such as steel or ceramic balls) to impact, rub, and shear materials, thereby achieving material crushing, refinement, or surface morphology control. Therefore, this embodiment provides a ball milling method to improve the volume stability and robustness of steel slag aggregates. Figure 1 As shown, it includes: S1: Steel slag aggregate with a particle size distribution range of the first particle size to the second particle size is placed into a planetary ball mill jar with a material-to-ball mass ratio of 0.1 to 1.3. The material is ball-milled at a revolution speed of 400 rpm to 600 rpm and a revolution-to-rotation speed ratio of 1:1 for 5 min to 15 min. S2: After ball milling, the steel slag aggregate is screened to separate the hard components whose particle size still falls within the original set gradation range, thus obtaining steel slag aggregate with improved volume stability and strength; wherein, any combination of the material-ball mass ratio, revolution speed and ball milling time satisfies the following conditions: the content of free calcium oxide in the hard components is not higher than 1.1% and the crushing value is not higher than 18%.
[0023] Specifically, planetary ball mills are widely used for fine surface treatment of particles due to their high energy input and more uniform grinding effect. By adjusting the process parameters (speed, time, ball-to-material ratio) of a small planetary ball mill, the impact force and direction of the grinding balls on the steel slag surface can be controlled. By controlling the magnitude of the force exerted by the grinding balls on the steel slag aggregate, the tangential friction and normal collision of the grinding balls on the steel slag aggregate can cause the dicalcium silicate (C2S) and tricalcium silicate (C3S) compounds adhering to the surface of the steel slag aggregate to break down and fall off, thereby peeling C2S and C3S off the steel slag surface. The free calcium oxide crystals previously encapsulated by C2S and C3S will be exposed. These free calcium oxide crystals have a small particle size and form a low interfacial strength with the steel slag aggregate surface. At this point, the tangential stress generated by the sliding and rolling of the grinding balls on the steel slag aggregate surface can peel off the free calcium oxide crystals from the steel slag aggregate surface. Because the surface of steel slag aggregate is subjected to repeated impacts and friction from the grinding balls, the exfoliated calcium oxide crystals are not easily adhered to the surface of the steel slag aggregate within its original particle size range. Instead, they tend to accumulate in crushed or pulverized aggregates with larger specific surface areas and fewer interactions with the grinding balls. This is because the surface of coarse steel slag aggregate is subjected to continuous high-frequency vibrations during ball milling due to the constant collisions with the grinding balls. This condition is unfavorable for f-CaO grains to embed into the surface of coarse aggregate. Some steel slag aggregate, after being crushed or pulverized, forms fine aggregate. The surfaces of these fine aggregates and pulverized particles are relatively rough, and the bonding force between them and the f-CaO grains is much greater than that between them and the surface of coarse aggregate. Therefore, fine powder is preferentially mixed into the crushed aggregate.
[0024] After the ball milling test, the fine steel slag aggregate enriched with free calcium oxide can be separated by manual sieving, ultimately improving the road performance of steel slag aggregate within the original particle size range.
[0025] In a specific embodiment, steel slag aggregate with a particle size distribution range of the first to the second particle size is placed in a planetary ball mill jar with grinding balls at a mass ratio of 0.1 to 1.3. The material is then ball-milled at a revolution speed of 400 to 600 rpm and a revolution-to-rotation speed ratio of 1:1 for a milling time of 5 to 15 minutes. In this embodiment, the diameter of the grinding balls is between 5 mm and 15 mm, the material-to-ball mass ratio is the ratio between the mass of the selected steel slag aggregate and the mass of the grinding balls, the first particle size is 4.75 mm, and the second particle size is 16 mm.
[0026] To determine the combination of process parameters that satisfies the above conditions, the following method was used to determine the ball milling time for each ball mass ratio and each revolution speed: First, a three-dimensional discrete element model of the mill jar and grinding balls is constructed. Aggregate particle models are generated based on fixed mass, gradation, and material-to-ball mass ratio, and then naturally stacked within the jar. The bulk density, Poisson's ratio, and coefficient of restitution of each model are determined according to the material properties of the mill jar, grinding balls, and steel slag.
[0027] Secondly, the dynamic and static friction coefficients between the material models were input, and different revolution speeds were set for slag mill simulation. After the particle model motion stabilized, the tangential collision energy loss between the grinding balls and the aggregate was recorded at each speed. A physical ball mill test was conducted with the same parameters, and the average roundness of the aggregate was measured under each condition after a certain time. Next, the tangential collision energy and average roundness data points were plotted with the rotation speed as the abscissa, and the Pearson correlation coefficient between the two types of data points was calculated. If the correlation coefficient was less than a threshold, the friction coefficient was adjusted until the threshold was met, completing the model calibration. Finally, based on the calibrated model, simulations were performed with multiple mass, gradation, ball mass ratio, and rotation speed combinations. After stabilization, the tangential and normal collision energies were extracted; a physical test was conducted under the condition where the tangential collision energy was higher than the set threshold for the normal collision energy.
[0028] Select a combination of ball mass ratio and revolution speed within the range of ball mass ratio of 0.1 to 1.3 and revolution speed of 400 to 600 rpm; For the same selected combination of ball mass ratio and revolution speed, multiple ball millings were performed for different durations within 5 min to 15 min, and samples were taken to detect the free calcium oxide content, crushing value, roundness of the hard component, and the free calcium oxide content of the fine powder under sieve. Determine whether the lowest value of the free calcium oxide content of the hard component is not higher than 1.1%, whether the lowest value of the crushing value is not higher than 18%, and whether the values are within the preset range. If any value exceeds the set value, the combination of the material ball mass ratio and the revolution speed is marked as an invalid combination. For combinations that fall within the numerical range, with the ball milling duration as the independent variable, the evolution curves of the above four indicators as a function of ball milling time are fitted respectively. The ball milling times corresponding to the lowest point of free calcium oxide content in the hard component, the lowest point of crushing value, the lowest point of roundness, and the highest point of free calcium oxide content in the fine powder under the sieve are extracted, and the average value of the four is taken as the ball milling time of the combination.
[0029] This embodiment provides a detailed explanation of a specific parameter determination process.
[0030] Step 1: Construct a discrete element model and calibrate the model parameters: Based on the material properties of the mill jar, grinding balls, and steel slag, the bulk density, Poisson's ratio, and coefficient of restitution of each discrete element model are determined to construct a three-dimensional discrete element model of the mill jar and grinding ball particles. A discrete element model of the steel slag aggregate particles is generated by fixing the mass, gradation, and mass ratio of the steel slag aggregate.
[0031] Specifically, loading tests were conducted on the actual grinding jar, actual grinding balls, and actual steel slag aggregate, respectively. The transverse strain and axial strain before cracking and failure of each actual object were recorded, and the ratio of transverse strain to axial strain was calculated. This ratio was used as the Poisson's ratio of the corresponding material. In this embodiment, the Poisson's ratio of the steel slag aggregate was 0.27, and the Poisson's ratio of the grinding jar and grinding balls was 0.31. Physical grinding balls, physical steel slag aggregate, and physical grinding jars were subjected to drop impact tests. The drop impact test refers to the mutual collision between the steel balls, steel slag, and the grinding jar. The process of each object falling from the start to the set rebound height was filmed. The instantaneous velocity of each object upon contact with the ground and the instantaneous velocity at the start of rebound were analyzed. The coefficient of restitution was calculated according to the following formula:
[0032] in, For the first The first material and the second The coefficient of restitution between the materials, dimensionless; For the first The first material contact The instantaneous velocity of the material, in m / s; For the first The instantaneous velocity of the material at the start of its rebound, in m / s. In this embodiment, the coefficient of restitution between the steel slag aggregate and the mill jar is 0.49, the coefficient of restitution between the mill jar and the grinding balls is 0.53, the coefficient of restitution between the grinding balls and the steel slag aggregate is 0.31, the coefficient of restitution between the grinding balls is 0.41, and the coefficient of restitution between the steel slag aggregates is 0.28. Obtaining the packing density between discrete elements is a conventional technique for those skilled in the art, therefore no detailed steps will be provided, as those skilled in the art will know how to obtain the packing density. Based on the determined bulk density, Poisson's ratio, and coefficient of restitution, a three-dimensional discrete element model of the mill jar and grinding balls is constructed. A discrete element particle model of the aggregate is generated using parameters such as fixed steel slag aggregate mass, gradation, and the mass ratio of the grinding balls to the aggregate. The grinding balls and steel slag aggregate particle models are then arranged to naturally stack within the jar.
[0033] Specifically, this embodiment uses EDEM discrete element method software to construct a three-dimensional discrete element model of the grinding jar and grinding balls based on the dimensions of the physical grinding jar and grinding balls. In this embodiment, the grinding jar is a hollow cylindrical model, such as... Figure 2 As shown, the hollow cylindrical section has a bottom diameter of 41.3 mm and a height of 101.9 mm. The grinding balls have a diameter ranging from 5 mm to 15 mm. Discrete element particle models of the aggregate are generated based on parameters such as the mass, gradation, and mass ratio of the steel slag aggregate. Figure 2The mass of the steel slag aggregate is 500g, the gradation is 5~10mm, and the mass ratio of the material to the ball mill is 0.4. After the steel slag particle model is generated, it naturally stacks inside the ball mill jar model.
[0034] Step 2: Conduct simulation experiments at different revolution speeds and record the tangential collision energy loss: With a fixed revolution-rotation speed ratio, different revolution speed conditions were set for the ball mill jar, and ball milling steel slag simulation tests were carried out respectively. The tangential collision energy loss between the discrete element model of the grinding ball particles and the discrete element model of the steel slag aggregate particles was recorded when the set particle model motion stability conditions were reached at each speed.
[0035] Specifically, different revolution speeds were set for the ball mill jar model according to a fixed speed ratio. In this embodiment, the speed ratio is 1, and the revolution speeds are 200 rpm, 300 rpm, 400 rpm, and 500 rpm. Simulation tests of ball mill steel slag were conducted under different revolution speed conditions.
[0036] In the simulation experiment of ball milling steel slag, the revolution period of the ball mill jar was used as the time unit. The total collision energy loss between the discrete element model of grinding ball particles and the discrete element model of steel slag aggregate particles was statistically analyzed in N consecutive revolution periods, denoted as . ; If, in any two adjacent orbital periods within the N consecutive orbital periods, the absolute value of the difference in total collision energy loss is less than a set threshold, then the following condition is met.
[0037] Then the particle model is determined to have reached a stable state, and the stable state is as follows: Figure 2 As shown, the threshold in this embodiment is 0.2J.
[0038] After the particle model motion stabilizes, record the tangential collision energy loss between the discrete element model of the grinding ball particles and the discrete element model of the steel slag aggregate particles at each rotation speed.
[0039] Step 3: Conduct a physical ball milling test and measure the average roundness: Grinding balls and actual steel slag aggregate are added to the actual ball mill jar according to the fixed steel slag aggregate mass, gradation and ball mass ratio. The actual steel slag ball milling experiment is carried out according to the set revolution speed conditions. After the actual test continues for a preset time, the average roundness of the actual steel slag aggregate with particle size maintained within the set gradation under each revolution speed condition is measured.
[0040] Specifically, a physical steel slag ball milling test was conducted using the same steel slag aggregate mass, gradation, and ball mass ratio parameters, along with the same revolution speed. After the physical ball milling test lasted for a specific time, the steel slag aggregate in the physical ball mill jar was sieved out. The roundness of the physical steel slag aggregate was measured, and the average roundness was calculated.
[0041] Step 4: Calculate the correlation coefficient and calibrate the model parameters: With the revolution speed as the abscissa, curves with tangential collision energy loss and average roundness data points as the ordinate are plotted. The Pearson correlation coefficient between tangential collision energy loss and average roundness data points is calculated, and the parameters of each discrete element model are calibrated based on the Pearson correlation coefficient. The parameter is the friction coefficient between the discrete element model of steel slag aggregate particles and the discrete element model of grinding ball particles.
[0042] Specifically, the tangential collision energy loss and average roundness data points are normalized using the following formula:
[0043] in, For the first The first normalized data in the class Data points, For the first The maximum value in the class data. For the first The minimum value in the class of data. For the first The first in the class data One data point; Calculate the Pearson correlation coefficient between the normalized tangential collision energy loss and the normalized average roundness data points; If the Pearson correlation coefficient is less than the set threshold, the rolling friction coefficient between the discrete element model of steel slag aggregate particles and the discrete element model of grinding ball particles is adjusted based on the normalized data. The formula is as follows:
[0044] in, The number of settings for the revolution speed. For the first Average roundness corresponding to each revolution speed; For the first Tangential collision energy loss corresponding to each revolution speed; The adjusted rolling friction coefficient, The original rolling friction coefficient was used. Plot the normalized tangential collision energy loss and average roundness data points using spline curves, and then differentiate these two spline curves. Find the revolution speed corresponding to the point of maximum derivative on the two curves. If the absolute value of the difference between the two revolution speeds is less than or equal to a threshold, maintain the current static friction coefficient; if it is greater than the threshold, adjust the static friction coefficient between the discrete element model of steel slag aggregate particles and the discrete element model of grinding ball particles according to the following formula:
[0045] in, The revolution speed corresponding to the point where the derivative of the spline curve of the average roundness data points is the maximum; The revolution speed corresponding to the point of maximum derivative on the spline curve of the tangential collision energy loss data points. The adjusted static friction coefficient; The static friction coefficient before adjustment; The ball mill slag simulation experiment was repeated until the Pearson correlation coefficient between the output tangential collision energy loss data points and the average roundness data points reached a threshold, thus calibrating the discrete element model parameters. The correlation coefficient is as follows: Figure 3 As shown, the Pearson correlation coefficient threshold specified in this embodiment is 0.95.
[0046] Step 5: Screening candidate operating conditions based on the calibration model: Based on the calibrated discrete element model parameters, ball milling simulation tests were conducted on steel slag under various combinations of steel slag aggregate mass, gradation, ball mass ratio, and revolution speed. The tangential and normal collision energy losses between steel slag aggregate particles and grinding ball particle models were extracted when each combination of working conditions reached the set particle model motion stability conditions. The combination of working conditions with tangential collision energy loss higher than the set threshold of normal collision energy loss was selected as candidate working conditions, and actual steel slag ball milling tests were conducted. Sampling was carried out at different ball milling durations.
[0047] Specifically, based on the calibrated model, ball milling simulation tests were conducted on steel slag with various combinations of aggregate mass, gradation, ball-to-particle mass ratio, and revolution speed. After the particle motion stabilized, the tangential and normal collision energy losses between the steel slag aggregate particles and the grinding ball particle model were extracted. Actual steel slag ball milling tests were conducted using operating parameters where the tangential collision energy loss exceeded a set threshold proportion of the normal collision energy loss. The tangential and normal collision energy losses under different operating conditions are shown below. Figure 4 As shown.
[0048] In this embodiment, a self-calibration method for the discrete element model based on the Pearson correlation coefficient of "tangential collision energy loss - average roundness" was established, which significantly improved the prediction accuracy of the simulation model for the ball milling process of steel slag aggregate. Planetary ball mills crush materials through the mechanical collision and friction between grinding balls and the material. Therefore, this invention uses tangential collision energy loss as the simulation output and the average roundness of the actual steel slag aggregate (within a set particle size distribution) as the actual response. By calculating the Pearson correlation coefficient between the two at different revolution speeds, and using this as a basis for iteratively adjusting the friction coefficient in the discrete element model, the parameters of the discrete element model are calibrated. The calibrated model can precisely control the impact direction and collision energy of the grinding balls on the steel slag aggregate, providing a reliable simulation basis for subsequent operating condition selection.
[0049] This embodiment uses the ratio of "tangential collision energy / normal collision energy" to screen candidate working conditions, achieving the goal of "retaining the difficult-to-grind components and separating the easily-grindable components" in steel slag aggregate, and effectively improving the road performance of the aggregate. By adjusting the grinding time and the collision energy of the grinding balls in a small planetary ball mill, the impact force and direction of the grinding balls on the steel slag aggregate can be controlled. Therefore, based on the calibrated discrete element model, this invention extracts the tangential and normal collision energy losses between the grinding balls and the steel slag aggregate under various working conditions, and uses a threshold ratio where the tangential collision energy loss is higher than the normal collision energy loss as a screening condition. By screening for working conditions where tangential collision energy is dominant, the tangential grinding effect of the grinding balls on the surface of the steel slag aggregate is enhanced, effectively removing free calcium oxide from the surface of the steel slag aggregate, while avoiding the overall fragmentation of the aggregate caused by excessive normal collision energy. This reduces the number of micro-cracks inside the steel slag aggregate, improves the physicochemical properties of the steel slag aggregate, and effectively enhances its road performance.
[0050] In a specific embodiment, after ball milling, the steel slag aggregate is screened to separate the hard components whose particle size still falls within the originally set gradation range, thus obtaining steel slag aggregate with improved volume stability and strength. The scheme in which any combination of the material-to-ball mass ratio, revolution speed, and ball milling time satisfies the condition that the content of free calcium oxide in the hard components is not higher than 1.1% and the crushing value is not higher than 18% is as follows: Step 1: Determine the ball milling time for each candidate operating condition: Within the range of ball mass ratio of 0.1 to 1.3 and revolution speed of 400 to 600 rpm, a combination of ball mass ratio and revolution speed was selected as the candidate working condition. For the same selected combination of ball mass ratio and revolution speed, multiple ball milling sessions were conducted for different durations within a range of 5 to 15 minutes, and samples were taken.
[0051] Specifically, for each candidate operating condition, the following steps are performed: Screening The candidate operating conditions have a duration of In the actual steel slag ball milling test, steel slag aggregates whose particle size was still within the range of the gradation parameters were selected and marked as... ; right Roundness and crushing value tests were conducted, and the results of the two tests were recorded separately. and ;Will Break it down until all of them are broken down. broken particles Particle size is smaller than the preset value; Steel slag aggregates whose particle size is not within the gradation parameter range are marked as... ,Will Break it down until all of them are broken down. broken particles Particle size is smaller than the preset value; In this embodiment, the preset value is 0.075mm; Referring to the "Determination of Free Calcium Oxide Content in Steel Slag by EDTA Titration and Thermogravimetric Analysis", the free calcium oxide content in the crushed steel slag was determined by... and A titration test of the free calcium oxide content was conducted to determine... and The content of free calcium oxide is labeled as follows: and Titration results of free calcium oxide content in steel slag aggregate under different working conditions are as follows: Figure 5 As shown; Using the duration of the physical experiment as the x-axis, respectively... , , and As the ordinate, plot , , and Data points; The spline curves were used to fit and connect the four types of data points to obtain the spline curves corresponding to the four types of data points. from Extracting the duration of the physical experiment corresponding to the lowest point of the spline curve. ,from Extracting the duration of the physical experiment corresponding to the lowest point of the spline curve. ,from Extracting the duration of the physical experiment corresponding to the lowest point of the spline curve. ,from Extracting the duration of the physical experiment corresponding to the highest point of the spline curve. ; determination The lowest point of the spline curve and Whether the minimum value of the spline curve is within the preset value range. If any condition does not meet the preset value range, the candidate working condition is deemed invalid, the candidate working condition is abandoned, or the actual ball milling test for different durations is repeated. That is, it is determined whether the lowest point value of the free calcium oxide content of the hard component is not higher than 1.1%, whether the lowest point value of the crushing value is not higher than 18%, and whether the values are within the preset value range. If any value exceeds the set value, the combination of the material ball mass ratio and the revolution speed is marked as an invalid combination, that is, the candidate working condition is invalid and the candidate working condition is abandoned. If all values meet the preset range, then the first value is determined according to the following formula. Ball milling time under various candidate operating conditions:
[0052] in, For the first The ball milling time under various candidate operating conditions.
[0053] By comparing the ball milling times for different ball mass ratios and revolution speeds, the combination of ball mass ratio and revolution speed corresponding to the minimum ball milling time is taken as the optimal process parameters for the ball milling treatment of steel slag aggregate.
[0054] Step 2: Sieving, Separation, and Detection Verification After ball milling, the steel slag aggregate is screened to separate the hard components whose particle size still falls within the original set gradation range (4.75 mm to 16 mm), thus obtaining steel slag aggregate with improved volume stability and strength.
[0055] Specifically, after the ball milling test, the fine steel slag aggregate enriched with free calcium oxide was separated by manual sieving, ultimately improving the road performance of the steel slag aggregate within the original particle size range. Among them, the fine powder separated by sieving had a particle size of less than 4.75 mm.
[0056] The hard component obtained from sieving was tested and verified. The hard component was crushed until all crushed particles had a diameter less than 0.075 mm. Referring to the standard "Determination of Free Calcium Oxide Content in Steel Slag by EDTA Titration and Thermogravimetric Analysis," a free calcium oxide content titration test was performed on the crushed hard component to determine its free calcium oxide content. Simultaneously, a crushing value test was conducted on the hard component to determine its crushing value.
[0057] This embodiment uses free calcium oxide content titration, roundness, and crushing value tests as evaluation methods to comprehensively determine the optimal process parameters that balance volume stability, improved strength, and aggregate quality: This embodiment conducts physical ball milling tests for different durations for each candidate working condition, and performs free calcium oxide content titration, roundness test, and crushing value test on the ball-milled steel slag aggregate. The ball milling time is determined by comprehensively considering the evolution of the three indicators. This evaluation system directly addresses the actual application requirements of steel slag aggregate in road engineering, ensuring that the finally determined optimal process parameters can effectively reduce the free calcium oxide content while maintaining the original advantages of low roundness and low crushing value of steel slag aggregate.
[0058] To verify the effectiveness of this invention, the actual steel slag ball milling test procedure is as follows: (1) Preparation stage: According to the ratio of steel slag mass to ball mass determined in the screening conditions, screen out steel slag aggregate with particle size within the specified range, and weigh steel slag aggregate within the same particle size range with the same mass as in the determined conditions. Start the ball mill and set the revolution speed to be consistent with the determined conditions.
[0059] (2) Ball milling test stage: The screened steel slag aggregate is placed in a ball mill jar, the jar is sealed and fixed on a planetary ball mill. The planetary ball mill is started and maintained for the same time as determined. After ball milling, the grinding balls are separated from the steel slag aggregate, and the steel slag aggregate in the ball mill jar is manually screened. Steel slag aggregate with particle size maintained within the original particle size range and steel slag aggregate with particle size smaller than the specified range are obtained.
[0060] (3) Titration test stage: According to the test specifications, free calcium oxide titration tests were conducted on steel slag aggregates with particle sizes maintained within the original particle size range and steel slag aggregates with particle sizes smaller than the specified range. The free calcium oxide content of the two types of steel slag aggregates was obtained.
[0061] (4) In the roundness test stage, a three-dimensional mechanical scanning test is performed on the steel slag aggregate whose particle size is kept within the original particle size range to obtain the length, width, height, surface area and volume of the aggregate, determine the particle size and shape parameters of the steel slag aggregate, and characterize the roundness of the aggregate.
[0062] Experiment 1: Following the above steps, experiments were conducted on combinations of different ball-to-material mass ratios (0.1, 0.3, 0.5, 0.7, 1.0, 1.3) and different revolution speeds (400 rpm, 500 rpm, 600 rpm). For each combination, step S1 involved ball milling with the corresponding parameters. Step S2 involved sieving to separate the hard components whose particle size still fell within the originally set gradation range. The free calcium oxide content of the steel slag aggregate before and after ball milling was determined by titration. The surface morphology of the untreated steel slag aggregate under a scanning electron microscope is shown below. Figure 5 As shown in Table 1, some results after ball milling are shown in Table 2, and the excluded results are shown in Table 2: Table 1. Working conditions that reduce free CaO content in steel slag aggregates
[0063] Table 1 shows the free calcium oxide content in steel slag aggregates under different particle size ranges, different ball-to-particle ratios, and different ball milling times at 400 rpm. The surface morphology of the ball-milled steel slag aggregates under a scanning electron microscope is shown below. Figure 6 As shown, Figure 7 This is a schematic diagram showing the average titration results of free calcium oxide content in parallel samples of steel slag aggregate ranging from 13.2 mm to 16 mm. Figure 8 A schematic diagram showing the average titration results of free calcium oxide content in parallel samples of steel slag aggregate ranging from 9.5 mm to 13.2 mm. Figure 9 A schematic diagram showing the average titration results of free calcium oxide content in parallel samples of steel slag aggregate ranging from 4.75 mm to 9.5 mm. From Table 1 and Figures 6-9 It can be seen that the free CaO content in the steel slag aggregate is significantly lower than that in the untreated steel slag aggregate, with the reduction ranging from 31.2% to 71.8%. This indicates that the ball milling process described above can effectively remove free CaO from the steel slag.
[0064] The results of the exclusion are shown in Table 2: Table 2. Operating conditions that increase free CaO content after ball milling (excluding those conditions)
[0065] Figure 7 -to Figure 9 In the above, the working conditions with a free calcium oxide content greater than 1.1% are excluded from the list of working conditions.
[0066] Experiment 2: The steel slag aggregate treated according to this invention was compared with the steel slag aggregate treated by natural weathering. The results are as follows: After the steel slag aggregate was naturally aged for 8 months, a free calcium oxide titration test was conducted on the aged steel slag aggregate. Some data are summarized in Table 3: Table 3 Free Calcium Oxide Content in Naturally Weathered Steel Slag Aggregate
[0067] The table shows that natural aging is not better than ball milling for removing free calcium oxide than natural aging.
[0068] Experiment 3: To demonstrate that the calcium oxide crystals after stripping are not easily adhered to the surface of steel slag aggregates within the original particle size range, but instead tend to accumulate in crushed or pulverized aggregates with larger specific surface areas and fewer interactions with grinding balls, the free calcium oxide content of steel slag aggregates with particle sizes smaller than the original particle size range was titrated. The titration results are shown in Table 4. Table 4. Free calcium oxide content of steel slag aggregates smaller than the original particle size range
[0069] As can be seen from Table 4, the free calcium oxide content in steel slag aggregates smaller than the original particle size range has a significant enrichment effect. Therefore, the present invention uses manual screening of steel slag aggregates smaller than the original particle size range, which can effectively separate free calcium oxide from steel slag aggregates that meet the requirements, thereby achieving the removal of free calcium oxide. Meanwhile, in this experiment, after ball milling the steel slag aggregate for 5 minutes, crushed steel slag aggregate with a particle size smaller than the original particle size range and fine steel slag powder were collected. XRD tests were then performed on the crushed steel slag aggregate and fine steel slag powder. The test results are as follows: Figure 10 As shown, from Figure 10 As can be seen from the electron microscope scan, the particulate matter of the steel slag aggregate consists of dicalcium silicate, tricalcium silicate, and calcium oxide.
[0070] Experiment 4: Crushing value test was conducted on steel slag aggregate treated under ball milling conditions. The results are as follows: Figure 11 As shown in the figure, the crushing value of the steel slag aggregate after ball milling is improved. This indicates that the "grindable components" of the steel slag aggregate are effectively destroyed, and the aggregate's resistance to crushing is improved.
[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A ball milling method for improving the volume stability and robustness of steel slag aggregate, characterized in that, include: S1: Steel slag aggregate with a particle size distribution range of the first particle size to the second particle size is placed into a planetary ball mill jar with a material-to-ball mass ratio of 0.1 to 1.
3. The material is ball-milled at a revolution speed of 400 rpm to 600 rpm and a revolution-to-rotation speed ratio of 1:1 for 5 min to 15 min. S2: After ball milling, the steel slag aggregate is screened to separate the hard components whose particle size still falls within the original set gradation range, thus obtaining steel slag aggregate with improved volume stability and strength; wherein, any combination of the material-ball mass ratio, revolution speed and ball milling time must meet the following conditions: the content of free calcium oxide in the hard components is not higher than 1.1% and the crushing value is not higher than 18%.
2. The ball milling method for improving the volume stability and robustness of steel slag aggregate according to claim 1, characterized in that, The ball milling time for each ball mass ratio and each revolution speed can be determined in the following ways: Select a combination of ball mass ratio and revolution speed within the range of ball mass ratio of 0.1 to 1.3 and revolution speed of 400 to 600 rpm; For the same selected combination of ball mass ratio and revolution speed, multiple ball millings were performed for different durations within 5 min to 15 min, and samples were taken to detect the free calcium oxide content, crushing value, roundness of the hard component, and the free calcium oxide content of the fine powder under sieve. Determine whether the lowest value of the free calcium oxide content of the hard component is not higher than 1.1%, whether the lowest value of the crushing value is not higher than 18%, and whether the values are within the preset range. If any value exceeds the set value, the combination of the material ball mass ratio and the revolution speed is marked as an invalid combination. For combinations that fall within the numerical range, with the ball milling duration as the independent variable, the evolution curves of the above four indicators as a function of ball milling time are fitted respectively. The ball milling times corresponding to the lowest point of free calcium oxide content in the hard component, the lowest point of crushing value, the lowest point of roundness, and the highest point of free calcium oxide content in the fine powder under the sieve are extracted, and the average value of the four is taken as the ball milling time of the combination.
3. The ball milling method for improving the volume stability and robustness of steel slag aggregate according to claim 1, characterized in that, The first particle size is 4.75 mm, and the second particle size is 16 mm.
4. The ball milling method for improving the volume stability and robustness of steel slag aggregate according to claim 2, characterized in that, The fine powder has a particle size of less than 4.75 mm.
5. A ball milling method for improving the volume stability and robustness of steel slag aggregate according to claim 2, characterized in that, By comparing the ball milling times for different ball mass ratios and revolution speeds, the combination of ball mass ratio and revolution speed corresponding to the minimum ball milling time is taken as the optimal process parameters for the ball milling treatment of steel slag aggregate.